PKM Pkm Pembelajaran Hafalan Hadis Di Pelita Hati Jakarta Selatan - Priyono, Priyono; Fiqhan Muslim , Ibnu; Ranam, Sanudin; Manurung, Lengsi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
This Community Service activity was carried out to provide training on techniques and how to memorize hadiths accurately and correctly to Pelita Hati Foundation students. Accompanying activities in learning to memorize hadiths focus more on how to memorize hadiths easily accompanied by the application of appropriate methods. Providing material by resource persons regarding learning to memorize hadiths will make it easier for students to memorize hadiths. The target of community service participants as planned was at least 5 – 10 participants, with 10 participants having an understanding of hadith. Based on the results and discussion of community service activities that have been explained previously, it can be concluded that the implementation of service activities at Pelita Hati, South Jakarta which was held in September 2023 – January 2024 in the hadith memorization learning activities has been carried out in the good category